2012
DOI: 10.1097/phm.0b013e31825ab5ec
|View full text |Cite
|
Sign up to set email alerts
|

Increases in Wheelchair Breakdowns, Repairs, and Adverse Consequences for People with Traumatic Spinal Cord Injury

Abstract: Objective The aims of this study were to report the current incidence of wheelchair breakdowns, repairs, and consequences and to compare current data with historical data. Design A convenience sample survey of 723 participants with spinal cord injury who use a wheelchair for more than 40 hrs/wk treated at a Spinal Cord Injury Model Systems center was conducted. Results Significant increases were found in the number of participants reporting repairs (7.8%) and adverse consequences (23.5%) in a 6-mo period (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 10 publications
1
31
1
Order By: Relevance
“…More than one-third of the study sample (35%) reported at least one repair in the previous 6 months, which falls in the range of earlier studies (Fitzgerald et al, 2005 ;McClure et al, 2009 ;Worobey et al, 2012). The results are similar to those of other studies wherein no significant relationship was found between the age of WCs and the number of repairs done (Fitzgerald et al, 2005).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…More than one-third of the study sample (35%) reported at least one repair in the previous 6 months, which falls in the range of earlier studies (Fitzgerald et al, 2005 ;McClure et al, 2009 ;Worobey et al, 2012). The results are similar to those of other studies wherein no significant relationship was found between the age of WCs and the number of repairs done (Fitzgerald et al, 2005).…”
Section: Discussionsupporting
confidence: 82%
“…injury) by 33% (n=109) of participants in one study (Gaal et al, 1997). Adverse consequences due to WC breakdown, such as being stranded at home, were reported by 20% -31% of participants who reported at least one repair (McClure et al, 2009;Worobey et al, 2012). Neither of these studies found correlation between WC age and the number of repairs (Fitzgerald et al, 2005;McClure et al, 2009).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…With a total of 2,213 subjects in their study, McClure et al found that 44.8 percent of fulltime wheelchair users required repairs over a 6 mo period [9]. Most recently, an article by Worobey et al reported failure rates of 52.6 percent from 726 subjects in the community [10]. The increasing rate of incidents, coupled with the time required to schedule and perform repairs, makes it clear that wheelchair reliability is getting worse and affects quality of life and safety.…”
Section: Introductionmentioning
confidence: 99%
“…These advances in design and manufacturing, along with the fact that the ANSI/RESNA durability standards have remained the same, should have resulted in higher quality, better durability, and cost-benefit. Nevertheless, as discussed earlier, wheelchair failures have been increasingly reported in the community over the last 15 yr [8][9][10].…”
Section: Introductionmentioning
confidence: 99%